2014
DOI: 10.15282/ijame.9.2013.21.0143
|View full text |Cite
|
Sign up to set email alerts
|

Modal Analysis of Dissimilar Plate Metal Joining with Different Thicknesses using MIG Welding

Abstract: This paper presents a study of the dynamic behavior of joining hybrid parts, stainless steel and aluminum alloy, by MIG welding. The objective is to analyze the effect of welding on dissimilar plates of stainless steel and aluminum. A finite element model of joining stainless steel and aluminum alloy by welding was built using a structural threedimensional (3D) solid modeling element. Impact testing using hammer excitation and accelerometer response measuring techniques was conducted to measure the vibration p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…They are characterised by high chromium (19-32%) and molybdenum (up to 5%) and lower nickel contents than austenitic stainless steels. The properties of duplex stainless steels are achieved with the overall lower alloy content than similar-performing super-austenitic grades, making their use cost-effective for many applications [3][4][5]. Arc welding is a type of welding that uses a welding power supply to create an electric arc between an electrode and the base material to melt the metals at the welding point.…”
Section: Introductionmentioning
confidence: 99%
“…They are characterised by high chromium (19-32%) and molybdenum (up to 5%) and lower nickel contents than austenitic stainless steels. The properties of duplex stainless steels are achieved with the overall lower alloy content than similar-performing super-austenitic grades, making their use cost-effective for many applications [3][4][5]. Arc welding is a type of welding that uses a welding power supply to create an electric arc between an electrode and the base material to melt the metals at the welding point.…”
Section: Introductionmentioning
confidence: 99%
“…There are quite a number of explorations done with regards to model updating technique. For example, several studies done previously have highlighted various methods of conducting model updating [16,22,[25][26][27][28][29][30]. Viewing updating parameter is an important subject and is the key of successful model updating.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of research has been done and reported on dissimilar welding [10][11][12]. Arguably the most famous research is on welding between aluminium and steel [2,[13][14][15][16][17][18]. The advantages include low cost and a weight-optimization body with high stiffness, reduction of material waste and energy saving [19].…”
Section: Introductionmentioning
confidence: 99%
“…The advantages include low cost and a weight-optimization body with high stiffness, reduction of material waste and energy saving [19]. To date, aluminium-steel welding has been performed using a vast number of welding methods, which include arc welding [15,[19][20][21], laser welding [22] and friction stir welding (FSW) [23]. In arc welding of aluminium-steel, previous studies show that tungsten inert gas (TIG) is preferable to metal inert gas (MIG) welding.…”
Section: Introductionmentioning
confidence: 99%